CmMYB#7, an R3 MYB transcription factor, acts as a negative regulator of anthocyanin biosynthesis in chrysanthemum. (17th April 2019) - Xiang, Lili; Liu, Xiaofen; Li, Heng; Yin, Xueren; Grierson, Donald; Li, Fang; Chen, Kunsong
Abstract : Flower color alterations often occur in ornamental plants. Changes in the expression of a dose-dependent anthocyanin repressor, CmMYB#7, accounts for this process in chrysanthemum. Abstract: 'Jimba', a well-known white flowered chrysanthemum cultivar, occasionally and spontaneously produces red colored petals under natural cultivation, but there is little information about the molecular regulatory mechanism underlying this process. We analysed the expression patterns of 91 MYB transcription factors in 'Jimba' and 'Turning red Jimba' and identified an R3 MYB, CmMYB#7, whose expression was significantly decreased in 'Turning red Jimba' compared with 'Jimba', and confirmed it is a passive repressor of anthocyanin biosynthesis. CmMYB#7 competed with CmMYB6, which together with CmbHLH2 is an essential component of the anthocyanin activation complex, for interaction with CmbHLH2 through the bHLH binding site in the R3 MYB domain. This reduced binding of the CmMYB6–CmbHLH2 complex and inhibited its ability to activate CmDFR and CmUFGT promoters. Moreover, using transient expression assays we demonstrated that changes in the expression of CmMYB#7 accounted for alterations in anthocyanin content. Taken together, our findings illustrate that CmMYB#7 is a negative regulator of anthocyanin biosynthesis in chrysanthemum.